Liraglutide via Activation of AMP-Activated Protein Kinase-Hypoxia Inducible Factor-1α-Heme Oxygenase-1 Signaling Promotes Wound Healing by Preventing Endothelial Dysfunction in Diabetic Mice - Huang, Huiya; Wang, Linlin; Qian, Fanyu; Chen, Xiong; Zhu, Haiping; Yang, Mei; Zhang, Chunxiang; Chu, Maoping; Wang, Xiaorong; Huang, Xiaozhong (Frontiers in Physiology, 2021)
Background/Aims: Diabetic foot ulcers (DFUs) present a major challenge in clinical practice, and hyperglycemia-induced angiogenesis disturbance and endothelial dysfunction likely exacerbate DFUs. The long-acting glucagon-like peptide-1 (GLP-1) analogue liraglutide (Lira) is a potential activator of AMPK that appears to enhance endothelial function and have substantial pro-angiogenesis and antioxidant stress effects. Therefore, in this study we aimed to investigate whether the protective role of Lira in diabetic wound healing acts against the mechanisms underlying hyperglycemia-induced endothelial dysfunction and angiogenesis disturbance. Methods: Accordingly, db/db mice were assessed after receiving subcutaneous Lira injections. We also cultured human umbilical vein endothelial cells (HUVECs) in either normal or high glucose (5.5 or 33 mM glucose, respectively) medium with or without Lira for 72 h. Results: An obvious inhibition of hyperglycemia-triggered endothelial dysfunction and angiogenesis disturbance was observed, follow by a promotion of diabetic wound healing under Lira treatment combined with restored hyperglycemia-impaired AMPK signaling pathway activity. AMPKα1/2 siRNA and Compound C (Cpd C), an inhibitor of AMPK, abolished both Lira-mediated endothelial protection and pro-angiogenesis action, as well as the diabetic wound healing promoted by Lira. Furthermore, Hif-1α (transcription factors of AMPK substrates) knockdown in HUVECs and db/db mice demonstrated that Lira activated AMPK to prevent hyperglycemia-triggered endothelial dysfunction and angiogenesis disturbance, with a subsequent promotion of diabetic wound healing that was Hif-1α–HO-1 axis dependent. Taken together, these findings reveal that the promotion of diabetic wound healing by Lira occurs via its AMPK-dependent endothelial protection and pro-angiogenic effects, which are regulated by the Hif-1α–HO-1 axis.